1993
DOI: 10.1007/bf02440865
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy of diclofenac dispersible and ibuprofen in postoperative pain after dental extraction

Abstract: We have compared single oral doses of drinkable diclofenac dispersible (50 mg) with ibuprofen (400 mg) and placebo in a randomized, double-blind, parallel-group trial in 127 adults complaining of at least moderately severe pain after removal of an impacted third molar. Within 40 min both diclofenac and ibuprofen produced significant pain relief that persisted for 6 h. There were no differences between diclofenac and ibuprofen in analgesic efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…These authors demonstrated an additive effect of paracetamol over the whole study period of 8 h. Their study also showed less use of rescue medication in the combination group compared with the patients treated with diclofenac alone, something also found in a study by Matthews et al (19). It would seem reasonable to assume that the additive effect of paracetamol in our study would be the same as in these two studies as rofecoxib and ibuprofen have been shown to have the same analgesic effect following third molar surgery (9,10,12) and the effects of ibuprofen and diclofenac are similar (30)(31)(32). It cannot be ruled out that there is a difference in additive effect of paracetamol when combining it with rofecoxib compared with diclofenac.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These authors demonstrated an additive effect of paracetamol over the whole study period of 8 h. Their study also showed less use of rescue medication in the combination group compared with the patients treated with diclofenac alone, something also found in a study by Matthews et al (19). It would seem reasonable to assume that the additive effect of paracetamol in our study would be the same as in these two studies as rofecoxib and ibuprofen have been shown to have the same analgesic effect following third molar surgery (9,10,12) and the effects of ibuprofen and diclofenac are similar (30)(31)(32). It cannot be ruled out that there is a difference in additive effect of paracetamol when combining it with rofecoxib compared with diclofenac.…”
Section: Discussionsupporting
confidence: 84%
“…(19). It would seem reasonable to assume that the additive effect of paracetamol in our study would be the same as in these two studies as rofecoxib and ibuprofen have been shown to have the same analgesic effect following third molar surgery (9, 10, 12) and the effects of ibuprofen and diclofenac are similar (30–32). It cannot be ruled out that there is a difference in additive effect of paracetamol when combining it with rofecoxib compared with diclofenac.…”
Section: Discussionmentioning
confidence: 57%
“…The proportion of participants with at least 50% pain relief was 54% (1000/1842) for ibuprofen 400 mg, and 12% (152/1244) for placebo; the RB was 4.4 (3.8 to 5.2), and the NNT was 2.4 (2.2 to 2.6). Fourteen studies had fewer than 40 participants in both treatment arms (Ahlstrom 1993; Ehrich 1999; Forbes 1984;Forbes 1990; Forbes 1991b; Forbes 1992; Hersch 1993b; Laska 1986; McQuay 1996; Nørholt 1998; Schwartz 2007; Seymour 1991 (study 1); Seymour 1991 (study 2); Seymour 1996) (Analysis 4.5.2). The proportion of participants with at least 50% pain relief was 60% (280/463) for ibuprofen 400 mg, and 14% (56/393) for placebo; the RB was 4.1 (3.2 to 5.2), and the NNT was 2.2 (1.9 to 2.5).…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of participants with at least 50% pain relief was 54% (1000/1842) for ibuprofen 400 mg, and 12% (152/1244) for placebo; the RB was 4.4 (3.8 to 5.2), and the NNT was 2.4 (2.2 to 2.6). Fourteen studies had fewer than 40 participants in both treatment arms (Ahlstrom 1993;Ehrich 1999;Forbes 1984;Forbes 1990;Forbes 1991b;Forbes 1992;Hersch 1993b;Laska 1986;Nørholt 1998;Schwartz 2007; (study 1); Seymour 1991 (study 2); Seymour 1996) (Analysis 4.5.2). The proportion of participants with at least 50% pain relief was 60% (280/463) for ibuprofen 400 mg, and 14% (56/393) for placebo; the RB was 4.1 (3.2 to 5.2), and the NNT was 2.2 (1.9 to 2.5).…”
Section: Ibuprofen 400 Mg: (Analysis 45)mentioning
confidence: 99%